(untitled) (Acta Scientiarum. Technology, 2014)
Thin layer air-drying experiments on passion fruit seeds were conducted and the effects of temperature and air-drying speed were investigated in a pilot air-dryer. Drying characteristics of passion fruit seeds were examined by heated ambient air at 40 and 60ÂºC and air-flow speed at 0.4 and 0.6 ms-1. Analysis of variance showed that the main effects were statistically significant for temperature (p < 5%) and for the interaction between air-speed and temperature (p < 5%). Diffusivity coefficient dependence with temperature was described by an Arrhenius-type equation. Diffusivity coefficient rates were 1.19 x 10-10 m2 s-1, at 0.9 m s-1 and 40ÂºC, to 1.55 x 10-10 m2 s-1 at 0.6 m s-1 and 60ÂºC. Activation energies were 13.3 and 14.2 kJ mol-1 for speeds 0.6 and 0.9 m s-1, respectively. Â